2005
DOI: 10.1051/0004-6361:20041125
|View full text |Cite
|
Sign up to set email alerts
|

Whole Earth Telescope observations of BPM 37093: A seismological test of crystallization theory in white dwarfs

Abstract: Abstract. BPM 37093 is the only hydrogen-atmosphere white dwarf currently known which has sufficient mass (∼1.1 M ) to theoretically crystallize while still inside the ZZ Ceti instability strip (T eff ∼ 12 000 K). As a consequence, this star represents our first opportunity to test crystallization theory directly. If the core is substantially crystallized, then the inner boundary for each pulsation mode will be located at the top of the solid core rather than at the center of the star, affecting mainly the ave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…This number is the sum of all the modes observed during various observing seasons. References: 1) Kepler et al (1995); 2) Bradley (1993Bradley ( , 2001; 3) Bradley (1998); 4) Bergeron et al (1993), Bradley (2001); 5) Kleinman et al (1998); 6) Robinson et al (1995), Bradley (1998); 7) Pfeiffer et al (1996); 8) Kanaan et al (2005), Metcalfe et al (2004), but see also Fontaine & Brassard (2004).…”
Section: Introductionmentioning
confidence: 99%
“…This number is the sum of all the modes observed during various observing seasons. References: 1) Kepler et al (1995); 2) Bradley (1993Bradley ( , 2001; 3) Bradley (1998); 4) Bergeron et al (1993), Bradley (2001); 5) Kleinman et al (1998); 6) Robinson et al (1995), Bradley (1998); 7) Pfeiffer et al (1996); 8) Kanaan et al (2005), Metcalfe et al (2004), but see also Fontaine & Brassard (2004).…”
Section: Introductionmentioning
confidence: 99%
“…We detect periods in J0840 ranging from roughly 180 to 800 s meanwhile pulsational periods of BPM 37093 lie in a narrow range of about 510 to 660 s (Kanaan et al 2005) and those of GD 518 range from 425 to 595 s (Hermes et al 2013). Our observed period range is consistent with the calculated period range for a 1.1 M CO-core WD with T eff = 12, 200 K presented in Figure 9 of Montgomery & Winget (1999), which shows the periods of l=2 modes for crystallized mass ratios ranging from 0 to 0.99.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies of BPM 37093, the most extensively observed high mass DAV, have encountered difficulty with mode identification since its modes are both low amplitude and undergo amplitude modulation (Kanaan et al 2005). Furthermore, amplitudes reported for GD 518 range from roughly 1 to 4 mma (Hermes et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A major glitch occurs when the interior nuclei settle into a crystal and lock up in zero point fluctuations much of the energy that could otherwise be radiated (Mestel & Ruderman 1967). For only one star is the crystallization expected within the ZZ Ceti strip, and its period spacing suggests that half or thereabouts of the interior has indeed crystallized (Kanaan et al 2005;Brassard & Fontaine 2005).…”
Section: White Dwarfsmentioning
confidence: 99%